Faktor-Faktor yang Mempengaruhi Perilaku Konsumen dalam Pengambilan Keputusan Pembelian di Alfamart Rawa Makmur Kota Bengkulu - Dhanu Anung Tri Kurniawan; Rossa Ayuni (Universitas Dehasen Bengkulu, 2022)
This research is motivated by the fact that there are still many people who are hesitant in making shopping decisions at Alfamart because it is influenced by several factors of their own behavior. This study aimed to determine the factors of affecting consumers’ behavior in making purchase decision at Alfamart Rawa Makmur of Bengkulu City. This type of this study was descriptive qualitative research with a total sample of 9 people during the study. The data collection techniques of this study usied observation, interview and documentation. The data analysis technique used data reduction, data presentation and drawing conclusion. The results of this study show that the factors of affecting consumers’ behaviorin making purchasing decision at Alfamart Rawa Makmur are promotional factors, product factors, price factors and location factors. There is a promotion for consumers when shopping at Alfamart Rawa Makmur.They are very satisfied and return to make transactions.